Hot Rolling of Magnesium Single Crystals - José Antonio Estrada-Martínez; David Hernández-Silva; Talal Al-Samman (Metals, 2021)
To analyze the effect of the initial orientation in the activity of twinning and texture development, magnesium single crystals were rolled at 400 °C (nominal furnace temperature) in two specific orientations. In both orientations, the rolling direction of the sheet (RD) was parallel to the c-axis. For orientation 1, the <semantics><mfenced close="]" open="[">11<mover accent="true">2¯</mover>0</mfenced></semantics> direction was parallel to the normal direction (ND), and for orientation 2, it was parallel to the <semantics><mfenced close="]" open="[">10<mover accent="true">1¯</mover>0</mfenced></semantics> direction. The samples were rolled at 30%, 50% and 80% of thickness reduction. After rolling, all the samples were quenched in water to retain the microstructure. The microstructure and texture evolution were characterized by X-ray diffraction and Electron Backscatter Diffraction (EBSD). The initial single crystals were turned into polycrystals, where most grains had their c-axis almost parallel to the ND, and this reorientation was explained by extension twinning. The active twin variants in orientation 1 aligned the basal plane ~30° from the sheet plane and caused a weaker basal texture compared to orientation 2, where the twin variants aligned the basal plane almost parallel to the sheet plane. Strain localization inside contraction twins was observed, and consequently, non-basal grains nucleated inside these twins and weakened the final basal texture only in orientation 1.